CORIVAL HYGIENE AND METABOLIC ADAPTATION - Тарасенко, Людмила; Рудь, Валентина; Войцехівський, Валерій (SWorldJournal, 2023)
The pre-term hygiene of one-year-old cows is even more important during the transition period (from the dry period to the postpartum period). Dairy cows undergo metabolic adaptations in the metabolism of glucose, fatty acids and minerals to promote lactat